PENGARUH SUNSET POLYCY. TAX AMNESTY, SANKSI PAJAK, E-SPT DAN KINERJA ACCOUNT REPRESENTATIVE TERHADAP TINGKAT KEPATUHAN PAJAK - Ashari Ashari; Afif Sadar Widodo; Ratih Hesty Utami (Universitas Muhammadiyah Semarang, 2017)
This study aims to determine the effect of Sunset Policy, Tax Amnesty, Tax Sanctions, e-SPT, and Performance Account Representative Against Taxpayer Compliance Level invCompliance with Obligation Studies On Taxpayers registered in the Office of Primary Tax Service Kudus. This study distributed questionnaires to Taxpayers registered in Tax Office Primary Kudus as much as 100 questionnaires. Sample selection technique in this research use random sampling. Data analysis methods used in this research are descriptive statistics, validity test, reliability test, classical assumption test, and hypothesis test. The results of this study concluded that Tax Amnesty, Tax Sanction, and e-SPT have a positive effect on Taxpayer Compliance Rate while Sunset Policy and Performance Account Representative have no effect on Taxpayer Compliance Rate. Keywords: Taxpayer Compliance, Sunset Policy, Tax Amnesty, Tax Sanctions, e-SPT, Performance Account Representative